Cross-sectional study of influenza trends and costs in Malaysia between 2016 and 2018 - Puteh, Sharifa Ezat Wan; Aazmi, Mohd Shafiq; Aziz, Muhammad Nazri; Kamarudin, Noor Adilah; Sam, Jamal I-Ching; Thayan, Ravindran; Mahiyuddin, Wan Rozita Wan; Mohamed Noor, Wan Noraini Wan; Cheong, Adelina; Guerche-Séblain, Clotilde El; Khor, Jean; Zamri, Eva Nabiha; et al. (Public Library of Science, 2024)
Background and objectives While influenza circulates year-round in Malaysia, research data on its incidence is scarce. Yet, this information is vital to the improvement of public health through evidence-based policies. In this cross-sectional study, we aimed to determine the trends and financial costs of influenza. Methods Data for the years 2016 through 2018 were gathered retrospectively from several sources. These were existing Ministry of Health (MOH) influenza sentinel sites data, two teaching hospitals, and two private medical institutions in the Klang Valley, Malaysia. Expert consensus determined the final estimates of burden for laboratory-confirmed influenza-like illness (ILI) and severe acute respiratory infection (SARI). Economic burden was estimated separately using secondary data supplemented by MOH casemix costing. Results Altogether, data for 11,652 cases of ILI and 5,764 cases of SARI were extracted. The influenza B subtype was found to be predominant in 2016, while influenza A was more prevalent in 2017 and 2018. The distribution timeline revealed that the highest frequency of cases occurred in March and April of all three years. The costs of influenza amounted to MYR 310.9 million over the full three-year period. Conclusions The study provides valuable insights into the dynamic landscape of influenza in Malaysia. The findings reveal a consistent year-round presence of influenza with irregular seasonal peaks, including a notable influenza A epidemic in 2017 and consistent surges in influenza B incidence during March across three years. These findings underscore the significance of continuous monitoring influenza subtypes for informed healthcare strategies as well as advocate for the integration of influenza vaccination into Malaysia’s national immunization program, enhancing overall pandemic preparedness.